Efektivitas AUM Umum sebagai Instrumen Penilaian Non-Tes untuk Mengidentifikasi Masalah Siswa - Nabila Rezky Palenza; Nurfarhanah Nurfarhanah; Zadrian Ardi (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
General AUM (General Problem Revealing Tool) is a non-test assessment instrument developed to identify problems experienced by students in various aspects of their lives, including personal, social, learning, family, and others. This study aims to determine the effectiveness of General AUM as an early identification tool in guidance and counseling services. The method used is a descriptive qualitative study with a literature review approach. The results of the study indicate that General AUM is effective as a non-test assessment instrument because it is able to dig up data widely, quickly, and systematically from the students' own perspectives. The use of General AUM also helps BK teachers in designing targeted services according to students' needs. However, its effectiveness is highly dependent on the counselor's interpretation skills and the students' openness in filling out the instrument.